2019
DOI: 10.1002/jcp.27705
|View full text |Cite
|
Sign up to set email alerts
|

Long‐noncoding RNA HOTAIR inhibits immunologic rejection of mouse leukemia cells through activating the Wnt/β‐catenin signaling pathway in a mouse model of leukemia

Abstract: Long‐noncoding RNAs (lncRNAs) is involved in the development of diverse diseases, including leukemia, while the role lncRNA HOX transcript antisense RNA (HOTAIR) played in leukemia remains unclear and in need of further investigation. Therefore, this study was conducted to explore the effects of lncRNA HOTAIR on the immunologic rejection of leukemia cells through the Wnt/β‐catenin in mice. Mice were administrated with HOTAIR mimics as well as small interfering RNA HOTAIR to explore the regulatory role of HOTAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In addition, exosomes may also promote tumor progression in hematological cancers. For example, elevated levels of the lncRNA HOX transcript antisense (HOTAIR) can lead to decreased T-lymphocyte proliferation as well as reduced immunoglobulin production and a reversed ratio of CD4 + /CD8 + T cell subsets through the Wnt/ β -catenin pathway, which may eliminate the immunologic rejection of leukemia cells [37]. Exosomal circRNAs from tumor cells play a crucial role in poor prognosis in cancer [38]; however, few studies have examined their interaction with the immune system.…”
Section: The Function Of Exosomes In the Tumor Microenvironment Anmentioning
confidence: 99%
“…In addition, exosomes may also promote tumor progression in hematological cancers. For example, elevated levels of the lncRNA HOX transcript antisense (HOTAIR) can lead to decreased T-lymphocyte proliferation as well as reduced immunoglobulin production and a reversed ratio of CD4 + /CD8 + T cell subsets through the Wnt/ β -catenin pathway, which may eliminate the immunologic rejection of leukemia cells [37]. Exosomal circRNAs from tumor cells play a crucial role in poor prognosis in cancer [38]; however, few studies have examined their interaction with the immune system.…”
Section: The Function Of Exosomes In the Tumor Microenvironment Anmentioning
confidence: 99%
“…Hu et al have conveyed that HOTAIR together with other factors facilitates OA development through the Wnt/ β-catenin pathway [7]. Another study also suggested that up-regulated HOTAIR might activate the Wnt/βcatenin signaling pathway [9]. Interestingly, a latest study performed that HOTAIR performs as a new repressor of calcification genes and is downregulated by Wnt/β-catenin pathway in human aortic valve cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, lncRNAs play a critical role in immune evasion. For example, HOTAIR not only promotes HLA-G expression to enhance the antigen presentation but also downregulates CD4+/CD8+ T-cell subsets (Figure 1; Table 1) (29, 30, 38), suggesting the dual effects of lncRNAs, which should be considered in future studies. These findings of immune-related lncRNAs in cancer immune regulation may provide potential theoretical strategies or novel approaches to overcome immune resistance through the manipulation of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%